Spatial distribution and ecological structure of Thalassia testudinum (Hydrocharitaceae) in two reefs of Veracruz Reef System National Park, Mexico - Arellano-Méndez, Leonardo (2016)
Seagrasses in coastal environments have been threatened by increased human activities; these have negatively altered processes and environmental services, and have decreased grassland areas. The aim of this study was to generate knowledge of Thalassia testudinum distribution, state of the structure and fragmentation level in two reefs of the Veracruz Reef System National Park (PNSAV). Two different reefs were selected: Sacrificios in the North and near the coast, and Cabezo in the South and away from the coast. Shoot-specific and area-specific characteristics of submerged macrophytes meadows present were determined, and four morpho-functional groups were identified. Significant differences between plant coverage were tested through nonparametric ANOVA, Kruskal-Wallis test. A supervised classification of spatial high-resolution image verified with field data was performed (55 Sacrificios and 290 Cabezo). The fragmentation level was calculated using landscape metrics, class level and thematic maps were made based on four covers. The meadows were dominated by Thalassia testudinum; maximum densities were 208 shoot/m2 in Cabezo, and 176 shoot/m2 in Sacrificios. Cabezo presented grasses with short (9 cm) and thin leaves (0.55 cm) on average; while Sacrificios showed longer (23.5 cm) and thicker (1 cm) leaves. Sacrificios showed lower fragmentation degree than Cabezo; in both cases, the vegetation cover fragmentation corresponded to less than 50 %. Although Cabezo reef presents further fragmentation, which creates a large number of microenvironments, being recognized for its importance as recruitment area. This work serves as a baseline for the creation of an adequate management plan (formation of a core area of Cabezo). It is necessary to complement this work with new efforts for the recognition of seagrass prairies in all PNSAV reefs, as well as periodic monitoring and recognition of ecosystem services.